THE ANTI-SECULAR TRADITION IN BRITISH HISTORIOGRAPHY: FROM HERBERT BUTTERFIELD TO MAURICE COWLING. - Green, S. J. D. (Fides et historia, 2012)
The article focuses on the influences of Christian historians Herbert Butterfield and Maurice Cowling in regards to British Christian historiography. The author discusses the success of Butterfield's book ''Christianity and History'' and what the author refers to as Butterfield's critique of intellectual arrogance in the book, which Butterfield refers to as ''mass cupidity.'' The author explores Butterfield's criticism of the destructive social and economic aspects of 20th century England, including amoral commercialism, capitalism and the industrial revolution.